2013
DOI: 10.1128/ec.00137-13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of White-Opaque Switching by Individual Subunits of Candida albicans Mediator

Abstract: The multisubunit eukaryotic Mediator complex integrates diverse positive and negative gene regulatory signals and transmits them to the core transcription machinery. Mutations in individual subunits within the complex can lead to decreased or increased transcription of certain subsets of genes, which are highly specific to the mutated subunit. Recent studies suggest a role for Mediator in epigenetic silencing. Using white-opaque morphological switching in Candida albicans as a model, we have shown that Mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 73 publications
1
50
0
Order By: Relevance
“…Cdk8/Ssn3 is a kinase that is part of the CDK8 module of Mediator, and it has been shown to modulate Mediator and transcription factor activity in ways that impact hyphal growth, switching, metabolism, and stress resistance (42,43,47,82). To directly determine if Cdk8 catalyzes the phosphorylation of Mediator subunits, we performed in vitro kinase assays using purified Mediator or mixtures of Mediator subcomplexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cdk8/Ssn3 is a kinase that is part of the CDK8 module of Mediator, and it has been shown to modulate Mediator and transcription factor activity in ways that impact hyphal growth, switching, metabolism, and stress resistance (42,43,47,82). To directly determine if Cdk8 catalyzes the phosphorylation of Mediator subunits, we performed in vitro kinase assays using purified Mediator or mixtures of Mediator subcomplexes.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type C. albicans Mediator complex was purified from cTTR03 through 6ϫHis-3ϫFlag-tagged Med8 (42). To allow for the affinity purification of Mediator complex from mutant strains, one or both copies of MED8 were fused to a sequence encoding a C-terminal 6ϫHis-3ϫFlag tag.…”
Section: Go Term Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatable CaMAL2 promoter was used to mitigate the toxicity of some constructs in the C. albicans reporter strain cRC106 (19). Our earlier work has shown that the CaMAL2 promoter functions independently of deletions in the Mediator tail module in C. albicans (20). Specifically, the CaACT1 promoter in CIp-LexA (19) was replaced by the CaMAL2 promoter by amplifying the CaMAL2 promoter from pSFS2 (21) using ZL179/ZL180.…”
mentioning
confidence: 99%
“…Furthermore, while the Mediator complex has conventionally been considered a transcriptional coactivator complex, acting as a dynamic interface between eukaryotic transcription factors and RNA polymerase II, recent evidence suggests a direct interaction between the Med5 and Med17 constituents of the Mediator complex with the histone H4 tail (41). Consistently, Mediator is required for the stability of the epigenetically repressed (white) and epigenetically active (opaque) morphological states of C. albicans (42). Hence, it is plausible that desilencing of several genes coding for members of the 23 EPA gene family, including EPA1 and EPA7, may account for the hyperadherence to the Lec2 cells observed upon deletion of the CgMED2 gene in C. glabrata ( Fig.…”
Section: Discussionmentioning
confidence: 66%